Four years in a red coat the Loveday internment camp diary of Miyakatsu Koike - Koike, Miyakatsu 1905-1998 (Wakefield Press, 2022)
This publication of an internee's personal diaries will expand our understanding of the civilian internment experience in Australia during World War II, through the words of a Japanese internee who spent four years behind the barbed wire at Loveday.The title of this book refers to the dyed red coats that were provided to Japanese and other internees in Australia.Miyakatsu Koike worked in 1941 for a Japanese bank in Indonesia (at the time known as the Dutch East Indies). When Japan entered World War II, he was arrested by Dutch authorities and, eventually, transferred to Australia's Loveday - the largest World War II internment camp in the country. Koike remained in Loveday until February 1946, and wrote a diary of his experiences during the war